Poetic effects : a relevance theory perspective - Pilkington, Adrian (Pragmatics & beyond, 2000)
Poetic Effects: A Relevance Theory Perspective offers a pragmatic account of the effects achieved by the poetic use of rhetorical tropes and schemes. It contributes to the pragmatics of poetic style by developing work on stylistic effects in relevance theory. It also contributes to literary studies by proposing a new theoretical account of literariness in terms of mental representations and mental processes. The book attempts to define literariness in terms of text-internal linguistic properties, cultural codes or special purpose reading strategies, as well as suggestions that the notion of lit.